Permainan Engklek dalam Menumbuhkan Karakter Kemandirian Anak Usia Dini - Elsya Usman; Siti Fadila Rajulali; Jumra U. Lahmutu; Sri Yunangsi Thalib (ICHIGO : Jurnal Bahasa, Sastra, Pendidikan, dan Budaya Jepang, 2024)
The traditional game of engklek has significant educational value in supporting character development and independence in children. Amid the increasing use of digital devices that have the potential to disrupt children's social, emotional, and physical development, engklek presents a positive alternative that encourages motor activity while simultaneously learning moral values. Using a literature review approach, this article examines the role of engklek in instilling character values, such as honesty, discipline, responsibility, cooperation, and nationalism. These values ​​are reflected through the game's rules, interactions between players, and the decision-making process during the game. Furthermore, playing engklek encourages children to develop independence, creativity, problem-solving skills, and communication skills in a fun social context. This game also contributes to strengthening social relationships, developing self-control, and fostering sportsmanship from an early age. By integrating physical activity, social interaction, and learning cultural values, engklek serves as an effective tool in supporting character education based on local culture. The findings of this study confirm that preserving traditional games is not only crucial for cultural sustainability but also relevant as an adaptive and meaningful educational strategy in the digital era.